Interferential current intensity influences the hypoalgesic response in healthy subjects under mechanically-induced pain: A randomized controlled trial. - Menezes, Mayara Alves; Mendonça Araújo, Fernanda; Lima, Lucas Vasconcelos; Souza, Thiago Abner Santos; Carvalho, Elyson Adan Nunes; Melo DeSantana, Josimari (Physiotherapy Theory & Practice, 2023)
Interferential current (IFC) is a non-pharmacological therapy often used to reduce pain intensity. However, there is no scientific evidence of the biological effects of the adjustment of IFC intensity of stimulation. To investigate whether the adjustment of IFC intensity influences pain on cutaneous sensory threshold (CST), pressure pain threshold (PPT) and pain intensity in healthy subjects under mechanically induced pain. This is a placebo-controlled randomized trial. One hundred and two healthy university students blinded to intervention were randomized using opaque sealed envelopes to the following groups: 1) sensory IFC (n = 24); 2) fixed motor IFC (n = 26); 3) adjusted motor IFC (n = 27); and 4) placebo IFC (n = 25). After 40 minutes of stimulation or placebo, subjects were evaluated by an investigator blinded to group allocation. CST (von Frey filaments), PPT (algometry), and pain intensity (11-point numerical scale) were measured. Adjusted motor IFC promoted a significant reduction of CST (hand: mean difference (MD) = 2.39, confidence intervals (CI) = 1.39–3.38; and forearm: MD = 3.01, CI = 2.87–3.14) compared to placebo. Adjusted motor IFC increased PPT significantly (hand: MD = 27.59, CI = 26.80–28.37; and forearm: MD = 34, CI = 25.74–42.25) when compared to placebo. Adjusted motor IFC reduced pain intensity by 4.01 points (CI = 3.64–4.55) when compared to placebo. No adverse events were observed. Adjusted motor IFC intensity increased PPT and CST and also reduced pain intensity in healthy subjects under mechanically induced pain.